Edukasi gizi menggunakan media cakram dalam meningkatkan pengetahuan ibu balita tentang kunjungan ke Posyandu - Lula Rulia Agustin; Betty Yosephin Simanjuntak; Anang Wahyudi (Poltekkes Kemenkes Aceh, 2023)
Background: One of the factors causing mothers' low number of visits to Integrated Healthcare (in Indonesia called Posyandu) is the lack of knowledge about Integrated Healthcare (IHC) visits, which impacts not detecting the nutritional status of children under five. Knowledge of mothers of toddlers is very important to improve the health of toddlers so that they can direct mothers to behave positively when visiting IHC.Objectives: The research aims to increase the knowledge of mothers of toddlers aged 24-59 months about visiting IHC using disc media at the Sawah Lebar Health Center, Bengkulu. Methods: Quantitative research using the Quasy experimental design was carried out at the Sawah Lebar Bengkulu Health Center from March to April 2023. The subjects involved were 40 mothers who were divided into two groups. The intervention used disc media and leaflet media with a Visit to IHC theme. Data was collected by interview using a ten-question questionnaire during the pre-test and post-test. The data obtained was tested using the Dependent T-test and Independent T-test parameters at a 95% confidence interval. Results: The difference in knowledge scores before and after being given education using disc media was 29,00. Meanwhile, education using leaflets obtained a difference in the average knowledge value of 21,50. There was an effect of nutritional education using disc media (p= 0,000) and leaflet media (p= 0,000) on increasing the knowledge of mothers of toddlers about visiting IHC. Conclusion: Nutrition education using disc media and leaflet media influences increasing the knowledge of mothers of toddlers about visiting IHC at the Sawah Lebar Bengkulu Health Center.